Field Line Resonances and Cavity Modes at Earth and Jupiter - Lysak, Robert L. (Frontiers in Astronomy and Space Sciences, 2022)
Ultra-Low-Frequency (ULF) waves provide a means for the rapid propagation of energy and field-aligned current in planetary magnetospheres. At Earth, the ULF frequency range is usually defined as including waves with periods of 0.2-600 seconds; however, at Jupiter these waves can extend to periods of tens of minutes. In both magnetospheres, shear mode Alfvén waves can form field line resonances that exist between the ionospheres, with periods of a few minutes at Earth and a few tens of minutes at Jupiter. A major distinction between these two magnetospheres is in the density distribution. Earth has a dense ionosphere full of heavy ions, an extended, cold plasmasphere and a relatively low-density plasma sheet. In contrast, at Jupiter, the ionosphere is largely hydrogen (both in atomic form and in the H3+ molecular ion), there is no appreciable plasmasphere and the plasma disk is dense and populated with heavy ions (largely sulfur and oxygen) originating at the moon Io and to some extent from other moons. As at Earth, the sharp Alfvén speed gradient above the ionosphere forms an ionospheric Alfvén resonator at Jupiter with periods of seconds. Furthermore, the high-latitude lobes at Jupiter have very low density and a resonant structure can be formed by waves bouncing between the ionosphere and the dense plasma disk. This structure leads to periods of tens of seconds. Finally, the dense Io plasma torus and plasma sheet provide conditions for compressional cavity modes to form in this region. Thus, the structure of the field line resonance modes is quite different at the two planets. Implications of these resonances on auroral particle acceleration will be discussed.